1979
DOI: 10.1128/jcm.10.4.497-502.1979
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal survey of the distribution of various serotypes of Streptococcus mutans in infants

Abstract: The establishment of various serotypes of Streptococcus mutans was studied serologically in plaque samples collected from labial surfaces of upper primary incisors of 22 infants (starting age, 5 to 13 months) over a period of 30 months. Clinical examinations were also performed. No clear-cut association between the initiation of dental caries and previous detection ofS. mutans was noted. However, all 12 of the infants with caries had S. mutans isolated at some time during the course of this study. The most com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
51
1
13

Year Published

1981
1981
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 16 publications
(17 reference statements)
7
51
1
13
Order By: Relevance
“…When examined separately, age, number of teeth, and bottle usage/content were each found to be associated with the presence of MS. The observation that the percentage of children colonized with MS increases with age and number of teeth also has been reported in previous studies of preschool children (7,27). However, since age, number of teeth, and bottle usage/content are related to one another as well as to MS colonization, the apparent associations between each of these variables and colonization with MS may have been confounded in the unadjusted analyses.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…When examined separately, age, number of teeth, and bottle usage/content were each found to be associated with the presence of MS. The observation that the percentage of children colonized with MS increases with age and number of teeth also has been reported in previous studies of preschool children (7,27). However, since age, number of teeth, and bottle usage/content are related to one another as well as to MS colonization, the apparent associations between each of these variables and colonization with MS may have been confounded in the unadjusted analyses.…”
Section: Discussionsupporting
confidence: 78%
“…The age at which a child becomes colonized is important since some studies suggest that the earlier mutans streptococci colonize a child's mouth the higher the caries experience (4,5). A recent study concluded that the acquisition of mutans streptococci occurs between 19 and 31 months of age (6), although other studies have reported that younger children may be colonized (7)(8)(9).…”
mentioning
confidence: 99%
“…The caries prevalences of the study populations in earlier longitudinal studies by CARLSSON et al (2) and MASUDA et al (5) were higher than in the present study, but so, too, were the isolation frequencies of S. mutans in corresponding age groups. These studies confirmed the relationship between the prevalence of S. mutans in the plaque and the development of caries.…”
Section: Discussioncontrasting
confidence: 65%
“…These studies confirmed the relationship between the prevalence of S. mutans in the plaque and the development of caries. The isolated S. mutans strains all belonged to serotype c/e/f, whieh was found to be the most common serotype group in many studies (5,10,19,20).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation